2019
DOI: 10.1021/acsnano.9b02993
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles from Cuttlefish Ink Inhibit Tumor Growth by Synergizing Immunotherapy and Photothermal Therapy

Abstract: Natural nanoparticles have been extensively studied due to their diverse properties and easy accessibility. Here, the nanoparticles extracted from cuttlefish ink (CINPs) with significant antitumor efficacy are explored. These CINPs, with spherical morphology, good dispersibility, and biocompatibility, are rich in melanin and contain a variety of amino acids and monosaccharides. Through the activation of mitogen-activated protein kinase (MAPK) signaling pathway, CINPs can efficiently reprogram tumor-associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(112 citation statements)
references
References 51 publications
5
107
0
Order By: Relevance
“…Among the protein sets, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis indicated that the most represented processes included tumor necrosis factor (TNF) signaling pathway, mitogen‐activated protein kinase (MAPK) signaling pathway, interleukin 17 (IL‐17) signaling pathway, and chemokine signaling pathway (Figure 7e), which are important pathways of immune system activation. [ 48 ] Particularly, in the protein sets belonged to MAPK signaling pathway, we found that the nuclear factor NF‐kappa‐B family proteins (Nfkb1 and Nfkb2), which play a key role in promoting M1 polarization, [ 49 ] significantly upregulated in response to Fe 3 O 4 ‐SAS@PLT treatment, suggesting that Fe 3 O 4 ‐SAS@PLT treatment might repolarize immunosuppressive M2 macrophages toward the antitumor M1 phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Among the protein sets, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis indicated that the most represented processes included tumor necrosis factor (TNF) signaling pathway, mitogen‐activated protein kinase (MAPK) signaling pathway, interleukin 17 (IL‐17) signaling pathway, and chemokine signaling pathway (Figure 7e), which are important pathways of immune system activation. [ 48 ] Particularly, in the protein sets belonged to MAPK signaling pathway, we found that the nuclear factor NF‐kappa‐B family proteins (Nfkb1 and Nfkb2), which play a key role in promoting M1 polarization, [ 49 ] significantly upregulated in response to Fe 3 O 4 ‐SAS@PLT treatment, suggesting that Fe 3 O 4 ‐SAS@PLT treatment might repolarize immunosuppressive M2 macrophages toward the antitumor M1 phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…As result, the synergistic therapy could effectively reverse the immunosuppressive tumor microenvironment and significantly control tumor growth in multiple tumor models in mice, extend survival rate and further protect them against malignant metastasis in late stage breast cancer. A similar approach, but based on the use of natural melanin-containing cuttlefish ink nanoparticles (CINPs), was followed by Deng et al who demonstrated an efficient synergistic PTT-immunotherapeutic approach for tumor growth inhibition [181]. In particular, CINPs reach in melanin, containing also various amino acids and monosaccharides, were extracted from the ink sac of cuttlefish using a differential centrifugation method (Figure 13).…”
Section: Ptt-immunotherapymentioning
confidence: 99%
“…Very recently, cuttlefish ink sac extracted nanoparticles (CINPs) comprising melanin, amino acids, and monosaccharides were obtained using a straightforward differential centrifugation method, and their antitumor efficacy by synergizing immunotherapy and PTT were investigated ( Figure ) 103. The polysaccharides from CINPs could facilitate the repolarization of tumor‐associated macrophages toward anti‐tumor M1‐like phenotype and motivate the infiltration of cytotoxic T cells within the tumor in vivo.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…* p < 0.05, ** p < 0.01, *** p < 0.001. Reproduced with permission 103. Copyright 2019, American Chemical Society.…”
Section: Biomedical Applicationsmentioning
confidence: 99%